BuShen HuoXue decoction improves fertility through intestinal hsp-16.2-mediated heat-shock signaling pathway in Caenorhabditis elegans - Wu, Kanglu; Zhao, Xudong; Xiao, Xian; Chen, Miao; Wu, Liang; Jiang, Chao; Jin, Jing; Li, Lei; Ruan, Qinli; Guo, Jun (Frontiers in Pharmacology, 2023)
BuShen HuoXue (BSHX) decoction is commonly used in the clinical treatment of premature ovarian failure because it can increase estradiol level and decrease follicle-stimulating hormone level. In this study, we determined the potential therapeutic effects of BSHX decoction via anti-stress pathway and the underlying mechanism by using the nematode Caenorhabditis elegans as an assay system. Bisphenol A (BPA, 175 μg/mL) was able to significantly decrease the brood size of C. elegans, so it was used to establish a fertility-defective C. elegans model. In BPA-treated N2 nematodes, 62.5 mg/mL BSHX decoction significantly improved the brood size and the oocytes quality at different developmental stages. BSHX decoction improved resistance to heat stress through the hsf-1-mediated heat-shock signaling pathway. Further analysis showed that the decoction significantly improved the transcriptional levels of hsf-1 downstream target genes, such as hsp-16.1, hsp-16.2, hsp-16.41, and hsp-16.48. Other than hsp-16.2 expression in the gonad, the decoction also affected intestinal hsp-16.2 expression and significantly reversed the adverse effects induced by BPA. Moreover, the decoction ameliorated intestinal ROS and permeability. Thus, BSHX decoction can improve fertility by increasing intestinal barrier function via hsp-16.2-mediated heat-shock signaling pathway in C. elegans. These findings reveal the underlying regulatory mechanisms of hsp-16.2-mediated heat resistance against fertility defect.